(untitled) (EAAE Annual Conference Proceedings, 2023)
The aim of the contribution is describing an urban design teaching activity developed in the last eight years (2016-2023) at one of the top Schools of Architecture in China: the Design Studios “Urban morphology, architectural typology, contemporary settlement patterns” held at the School of Architecture in Southeast University Nanjing, China.